Wanting HIV Is 'Such a Hot Choice': Exploring Bugchasers' Fluid Identities and Online Engagements. Issue 10 (2nd October 2020) - García-Iglesias, Jaime
ABSTRACT: Bugchasers are gay men who fetishize HIV infection and use the internet to discuss their fetish. Previous research considered bugchasers' online engagements as proof of their sexual identities. This paper contests that view the through the exploration of three cases: Scott, a committed bugchaser; Marvin, who uses the internet as 'bugchasing entertainment' but is not a bugchaser; and Milo, whose bugchasing feelings are blurry and evolving. All three men use the internet in diverse significant ways from pure entertainment to it being a key part of their daily life. In presenting and analysing these three cases, this paper complicates identity-based assumptions of bugchasing, and presents ways in which gay men engage with social media in the pursuit of sexual pleasure.